The implementation of cloud accounting in public sector - Aini Aman; Nahariah Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2017)
Past studies on cloud services revealed that there are several challenges faced by the organization in using cloud accounting. The main objective of this study is to understand the implementation of cloud accounting as the latest technology in Accounting Information Systems (AIS) in public sector. This study employs an interpretive case study for a better understanding of cloud accounting application in AIS. Data collection was conducted by interviewing a total number of seventeen directors and deputy directors who are directly involved in the implementation of cloud accounting in the public sector. By using system implementation framework, this study found that in the implementation of cloud accounting, challenges are associated with system specification which include system integration, security and privacy. Other challenges are associated to the roll out strategy and data migration. Theoretically, this study contributes to Information System Implementation framework in the context of new technologies implementation in public sector accounting. Practically, these findings increase the understanding and knowledge of accountants as a result, increase efficiency by providing accurate information to decision makers.